2022
DOI: 10.7554/elife.74114
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding remodels protein side-chain conformational heterogeneity

Abstract: While protein conformational heterogeneity plays an important role in many aspects of biological function, including ligand binding, its impact has been difficult to quantify. Macromolecular X-ray diffraction is commonly interpreted with a static structure, but it can provide information on both the anharmonic and harmonic contributions to conformational heterogeneity. Here, through multiconformer modeling of time- and space-averaged electron density, we measure conformational heterogeneity of 743 stringently … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 60 publications
(89 reference statements)
5
57
0
Order By: Relevance
“…We decompose the binding entropy into two terms, ∆S = ∆S conf + ∆S 0 , where ∆S conf is the change in conformational entropy, [41][42][43] which depends on the elastic network topology and spring stiness, and ∆S 0 accounts for other contributions to entropy that are not captured directly by the model (e.g., release of frustrated solvent, ligand conformational change, protein entropy change due to plastic deformation). 24,[44][45][46][47][48][49] We calculate ∆S conf for the elastic network by creating sti bonds of strength K Λ between the protein and ligand binding sites (see Methods). Standard normal mode analysis shows that the resulting entropy change is the sum over the variation in the logarithms of the mode energies λ i before and after binding, ∆S conf = − 1 2 i ∆ ln λ i .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We decompose the binding entropy into two terms, ∆S = ∆S conf + ∆S 0 , where ∆S conf is the change in conformational entropy, [41][42][43] which depends on the elastic network topology and spring stiness, and ∆S 0 accounts for other contributions to entropy that are not captured directly by the model (e.g., release of frustrated solvent, ligand conformational change, protein entropy change due to plastic deformation). 24,[44][45][46][47][48][49] We calculate ∆S conf for the elastic network by creating sti bonds of strength K Λ between the protein and ligand binding sites (see Methods). Standard normal mode analysis shows that the resulting entropy change is the sum over the variation in the logarithms of the mode energies λ i before and after binding, ∆S conf = − 1 2 i ∆ ln λ i .…”
Section: Resultsmentioning
confidence: 99%
“…Our model treats deformations as elastic, so it may not generalize well to proteins that undergo plastic deformations upon binding. In fact, the restructuring of intramolecular bonds can result in a gain in entropy 24,44 , or an increase in internal enthalpy. 117 Furthermore, a simplifying assumption in elastic network models is that bonds are at their equilibrium lengths in the ensemble-average protein structure.…”
Section: Examiningmentioning
confidence: 99%
See 1 more Smart Citation
“…We associate this fact with the higher molecular weight of this protein, as EGFR has a MW of 69.8 kDa, making it much bigger than EpCAM (with a MW of 29 kDa). Additionally, it is well-known that protein conformation influences inding affinity by affecting the free binding sites [ 44 ]. Similarly, it has been shown that the anion specific conformation can be used to control protein adsorption/desorption on the surface of PSBMA brushes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the dynamic nature of proteins is exploited in ligand binding. 10 Different receptor conformations can bind different ligand chemotypes, perhaps best exemplified by the "DFG-in" and "DFG-out" states occupied in different ratios by many protein kinases. 11 Docking a ligand to a rigid receptor conformational substate that deviates from its native bound state (e.g., an apo state) can result in inaccurate predictions of the bound complex that are not useful for further drug design applications.…”
Section: Introductionmentioning
confidence: 99%